AKTUALISASI SISTEM NILAI DALAM BUDAYA ORGANISASI PADA MADRASAH BERPRESTASI DI KOTA MALANG - Marno, Marno (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2010)
Providing education in both public and private schools can’t be separated from values, behavioral norms, beliefs and culture. Moreover, the schools run by religious foundations that nuance of course not merely seen as worldly matters, but also practice ukhrowi (religious), then the understanding of course can’t be separated from values of religious teachings. The values found in the organizational culture at the Madrasah achievers in Malang include: (a) the basic values of Islam which include: Tauhid (Oneness of Allah); worship (devotion) and the unity between the world of the Hereafter, (b) the values of citizens schools which include: jihad (struggle); trust (responsibility); sincere; ikhsan (quality); discipline; exemplary; brotherhood and kinship and values of students in academic increase.